To the Fiftieth Anniversary of the Department of Algebra and Mathematical Logic of Kyiv Taras Shevchenko University - Bezushchak, O.O.; Drozd, Yu.A.; Gorodniy, M.F.; Petravchuk, A.P.; Sushchanskiy, V.I. (Algebra and Discrete Mathematics, 2010)
History of algebraic research in Kyiv University starts in 1902 when